MENJAGA LINGKUNGAN BERSAMA PANTI ASUHAN CINTA IKHLAS KASIH - Gaberiel Riskia Surbakti; Randa Putra Kasea Sinaga (JOURNAL SAINS STUDENT RESEARCH, 2024)
Field Work Practice or PKL is a learning activity carried out by placing students in a company, industry, or agency. By participating in PKL activities, students will get direct experience of how the real world of work is while strengthening the mastery of students' technical competencies in accordance with their Expertise Competencies. Field Work Practice (PKL) is a compulsory subject for all Social Welfare students, Faculty of Social and Political Sciences, University of North Sumatra, where this PKL is Practicum II for students who are in semester 7. This activity was also carried out by one of the students of the Social Welfare Study Program, namely Gaberiel Riskia Surbakti NIM 200902101, located at the Cinta Ikhlas Kasih Indonesia Orphanage, Jln. Parang IV No.18, Kwala Bekala, Medan Johor District, Medan City. This activity was carried out for 3 months with a program to protect the environment. Protecting the environment is very important because the cleanliness of the environment will affect the health of children. Not only that, a clean environment can increase academic scores and maintain children's mentality. Protecting the environment can be done by not littering, not burning waste, saving energy, using recycled products and reducing waste. This program uses group work methods, namely: engagement stage, contract intake, assessment stage, planning stage, intervention stage, evaluation stage and termination stage.